2019
DOI: 10.1093/ageing/afz042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral neuromuscular training on swallowing dysfunction among older people in intermediate care—a cluster randomised, controlled trial

Abstract: Objectives this prospective, cluster randomised, controlled trial investigated the effect of oral neuromuscular training among older people in intermediate care with impaired swallowing. Methods older people (≥65 years) with swallowing dysfunction were cluster randomised according to care units for 5 weeks of neuromuscular training of the orofacial and pharyngeal muscles or usual care. The primary endpoint was the change in swallowing rate (assessed with a timed water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…As Table 1 shows, only one study used a qualitative design [ 41 ], and the topic was related to feeding experiences from nursing aides. Two studies were randomized controlled trials [ 29 , 42 ]. Three were classified as pseudo randomized controlled trials and another three were quasi-experimental studies [ 25 , 31 , 34 , 37 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Table 1 shows, only one study used a qualitative design [ 41 ], and the topic was related to feeding experiences from nursing aides. Two studies were randomized controlled trials [ 29 , 42 ]. Three were classified as pseudo randomized controlled trials and another three were quasi-experimental studies [ 25 , 31 , 34 , 37 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…As Table 1 shows, of the nineteen studies [13,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], six were conducted in the USA, three were conducted in Japan, two were conducted in Australia, and one was conducted in the UK, France, Sweden, Brazil, South Korea, Mainland China, Hongkong and Taiwan, respectively. Most were conducted in developed countries or regions (89.5%).…”
Section: Country or Region For Publicationmentioning
confidence: 99%
“…This suggested that patients with dysphagia could use an oral device to self-train their weak oral and pharyngeal muscles; that is, for neuromuscular training. Improvement in swallowing function has been reported among older people with dysphagia after oral neuromuscular training [ 9 ]. Until now, no randomized, controlled study has been performed to investigate the effect of oral neuromuscular training as treatment for post-stroke dysphagia.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that patients with dysphagia could use an oral device to selftrain their weak oral and pharyngeal muscles; that is, for neuromuscular training. Improvement in swallowing function has been reported among older people with dysphagia after oral neuromuscular training [9]. Until now, no randomized, controlled study has been performed to investigate the effect of oral neuromuscular training as treatment for poststroke dysphagia.…”
Section: Introductionmentioning
confidence: 99%